Rural productive inclusion and sustainable (agri-)food systems: the geography of transitions - Tartaruga, Iván Gerardo Peyré; Diniz, Paulo Cesar Oliveira; Perafán, Mireya Eugenia Valencia; Avila, Mário Lucio de (Sustainability in Debate, 2025)
The transition to sustainable food systems can provide opportunities for the productive inclusion of people in situations of exclusion, especially in rural areas, and contribute to reducing the effects of the climate crisis. This study aims to understand productive and sustainable inclusion cases in rural areas and verify the role of public policies. The experiences studied in two regions of the Brazilian Northeast characterise innovation niches, highlighting the generation of new technical and social solutions that trigger a transition to sustainable and inclusive food systems. Using a quali-quantitative methodology, we analysed the cases’ socio-technical configurations (STCA) within the scope of transition studies and network analysis. The results show the importance of family farmers’ cognitive and organisational capacities. In conclusion, policies supporting these emerging niches must be strengthened according to the territorial context. Finally, mitigating the adverse effects of external environmental technologies, such as wind energy, on rural communities is essential.